The impact of postharvest research - Goletti, Francesco; Wolff, Christiane (International Food Policy Research Institute, 1999)
While research on the improvement of agricultural production has received considerable attention and funding, until recently postharvest activities have not attracted much attention from international research organizations. However, there is an emerging consensus on the critical role that postharvest systems can play in meeting the overall goals of food security, poverty alleviation and sustainable agriculture particularly in developing countries. This study provides preliminary evidence on the impact of postharvest research on these goals; furthermore the study argues that postharvest research at international agricultural research organizations is justified by its international public good nature.